Effect of Infrastructure Development on the Rate GDRP in Daerah Istimewa Yogyakarta Province in 2012-2022 - Chabibi, Wahyu Nur; Sishadiyati, Sishadiyati (PT. Riset Press International, 2024)
Economic growth is an indicator of the success of a country's development. On a regional scale, economic growth parameters can be seen from the growth of Gross Regional Domestic Product (GRDP) per capita. DIY Province is one of Indonesia's provinces designated as a National Tourism Strategic Area (KSPN) by the Ministry of Tourism. Daerah Istimewa Yogyakarta (DIY) is a tourist destination with high economic productivity. This, of course, must be supported by the availability of adequate infrastructure. Therefore, this research aims to determine the effect of road, electricity, and water infrastructure development on GRDP rates in DIY Province. The data that has been obtained is analyzed using multiple linear regression. The results of this research show that the development of road infrastructure and electricity significantly influences the rate of GRDP in DIY Province. Meanwhile, the development of clean water infrastructure does not significantly affect the rate of GRDP.